Couples' Communication Behaviour and the Gender Division of Family Work Across the Transition to Parenthood. (April 2023) - Büchau, Silke; Schober, Pia S.; Becker, Dominik
This study investigates the conceptual argument that constructive and explicit couple communication may reduce gender inequalities in couples' division of family work. We focus on the transition to parenthood which for most couples in Germany results in a shift towards a more traditional division of labour. Using 314 first-time parents from the German Family Panel, we apply growth curve models to assess whether partners' prenatal characteristics explain the division of housework and childcare around the time of childbirth and in the following years. After controlling for gender ideologies and economic resources, male partners' frequency of positive communication is associated with greater father involvement in housework and childcare from the start. However, neither men's nor women's communication behaviours dampen the shift towards a more traditional division of housework and childcare in the first years after childbirth. The frequency of negative communication does not correlate with the division of family work.